CFTR complex alleles and phenotypic variability in cystic fibrosis disease: CFTR complex alleles - El-Seedy, Ayman; Ladeveze, Véronique (Cellular and Molecular Biology, 2024)
Cystic fibrosis (CF) is inherited by CFTR (cystic fibrosis transmembrane conductance regulator) gene mutations. A variety of mutations have been identified in the CFTR gene that may be associated with cystic fibrosis, and these mutations demonstrate extensive molecular genetic heterogeneity in this disease. Little is known about the molecular mechanism by which mutations affect CFTR function, and only a minority of mutations have been characterized by functional studies. There has been an increase in the number of complex alleles. This may partly explain the difficulty in establishing genotype-phenotype correlations and complicate genetic counseling and diagnosis in some cases. Therefore, the identification of complex alleles has several important implications for recessive disorders. This will facilitate diagnosis; improve judgements concerning prognosis, and enable appropriate genetic counselling for affected families. This review describes the complex cystic fibrosis allele to better understand the contribution of this allele in the wide phenotypic variability of cystic fibrosis disease. It occurs in the complex allele that the second cis mutation can modulate the effects of the first mutation or vice versa. The phenotypic variability between CF or CFTR-RD (CFTR related disease) patients may be due to several factors, including different genetic and environmental backgrounds. It is important to determine the allele complex so that optimal treatment can be established.